Approximation of complex organic tissue for investigation of the electromagnetic impact. Issue 4 (26th June 2019) - Frivaldsky, Michal; Pavelek, Miroslav; Spanik, Pavol; Faktorova, Dagmar; Spanikova, Gabriela
Abstract : Purpose: The purpose of this paper is to study the performance of the approximated model of biological tissue for development of complex 3 D models. The comparison of results from the complex model of liver tissue and results from the approximated model is provided to validate the proposed approximation method. Design/methodology/approach: The proposed model of hepatic tissue (respecting its heterogeneous character up to the microstructure of hepatic lobules) is used for analysis of current field distribution within this tissue. Initially, the complex model of tissue structure (respecting the heterogenous structure) is presented, considering its complicated structure. Consequently, the procedure for the approximation of a complex model is being described. The main motivation is the need for simple, fast and accurate simulation model, which can be consequently used within more complex modeling of human organs for investigation of negative impacts of electrosurgical equipment on heterogenic tissue structure. For these purposes, the complex and approximated model are mutually compared and evaluated. Findings: The obtained results are exploitable for the analysis of the probability of injury formation in sensitive tissue structures, and the approximated model shall serve for optimization of complex and time-consuming analyses. Research limitations/implications: Research limitations include development of precise and fast electro-magnetic simulation model of biological tissue. Practical implications: Practical implications is focused on the optimization processes of the electro-surgical procedures. Originality/value: The originality of the paper concerns the approximation method of organic tissue modeling.